EFEKTIVITAS MATA KULIAH BAHASA INGGRIS DI PGSD TERHADAP KEYAKINAN DAN MOTIVASI MAHASISWA DALAM MENGAJAR BAHASA INGGRIS SDHonest - Kaltsum, Honest Ummi; Setyawan, Heru; Krisnawan, Dika Adi (Universitas Muhammadiyah Surakarta, 2015)
This research aims to investigate the effectiveness of four English courses at PGSD FKIPUMS towards the belief and motivation of the PGSD students to teach English to primarystudents. From the 130 questioners distributed, 130 are also returned, and the workingquestioners are just 125. Based on the results of the descriptive analysis shows that thosefour courses have been effective (mean statistic above 3 and mode 4). While the variablemode of beliefs have mean values above 3 and largely mode 3. These results indicate thatthe respondents have confi dence in moderate level to teach English to their students. Studentresponses regarding motivation in teaching English showed that students have the motivationin teaching English, but the motivation is on moderate level. This is showed by the mean scoreswhich is above 3 and most of the modes is 3. The results of the descriptive analysis showedthat students still require the need for additional training to teach English to prospectivestudents. These results indicated by the mean score of 4 and mode 4. From this data, it can beseen that the students needs an additional training to make them ready teaching English toChildren. The conclusion is the program of four English courses has been effective, howeverthe students is in the moderate level of belief and motivation to teach English to primarystudents, therefore the additional English course training for those students is needed.